A Mona effect: How place discourse constitutes culture‐led change. (3rd August 2020) - Booth, Kate; Ragaini, Bruna Silva; Hardy, Anne
Abstract: The arrival of the Museum and Old and New Art (Mona) in the disadvantaged municipality of Glenorchy was heralded as the beginning of significant social change in Australia's island state of Tasmania. These expectations were premised on a local place discourse known as the "Tasmanian gothic, " and, in this article, our aim is to illustrate the importance of place specifications in culture‐led change, including in relation to how place discourse constitutes such change. To do this work, we illustrate a Mona effect that comprises a critical account of the Tasmanian gothic informed by an empiric of tourist movement to and from Mona. We demonstrate that tourist movements follow existing socio‐spatial patterns, with tourists from higher socio‐economic backgrounds bypassing Glenorchy and those from lower socio‐economic backgrounds more likely to stop in this disadvantaged municipality. This socio‐spatial account unsettles the characterisation of Tasmania and Tasmanians provided by the Tasmanian gothic and we conclude by observing (1) a lack of significant social change resulting from Mona, in part explained by well‐established socio‐economic patterns; (2) signs of more subtle change that warrant further investigation; and (3) how local place discourse can act to curtail culture‐led change by reinforcing existing socio‐economic patterns.